Fawlty powers: one-star service in the English courts - Dickinson, A (Informa Business Intelligence, 2018)
In his lifetime, Sir Ian Brownlie made inestimable contributions to learning and practice in the field of public international law. His untimely and unfortunate death kindled litigation that has cast an unedifying light upon the English civil justice system and, in particular, upon the rules applied by the English courts to assert adjudicatory jurisdiction over persons not resident or present at the time of commencement of proceedings. 1 The Supreme Court’s decision in Four Seasons Holdings Inc v Brownlie 2 serves as a beacon signalling the need for reform, if nothing else. Sir Ian and Lady Brownlie had visited Egypt in 2008, staying at the Four Seasons Hotel Cairo at Nile Plaza. 3 On that occasion, she picked up a leaflet advertising tours promoted by the hotel, and inviting guests to call the hotel concierge to make a reservation. In December 2009, before departing for a further stay at the hotel with her husband and family members, Lady Brownlie called the concierge from her home in England. She booked a tour to visit local sites, including provision of a car, a driver, a tour guide, a police escort and lunch. The cost of the tour was to be added to her hotel bill. Tragically, the car left the road and crashed, killing Sir Ian and his daughter, Rebecca, and injuring Lady Brownlie and Rebecca’s two children. Lady Brownlie instructed English solicitors, who, in June 2010, wrote a letter before action to the legal department of “Four Seasons Hotels and Resorts” in Canada. After that department had forwarded the correspondence to the hotel in Cairo and to the vehicle hire company, the Egyptian legal representatives of the hotel responded that the proper defendant was neither “Four Seasons Hotels and Resorts” nor “the Four Seasons Hotel, Cairo at Nile Plaza” but the vehicle hire company and its driver. The correspondence dragged. Lady Brownlie’s solicitors sought, but were not provided with, further information concerning the underlying legal entities. More than two years after the letter before action, a claim was issued on Lady Brownlie’s behalf in the English High Court. The claim form named two defendants, Four Seasons Holdings Incorporated (“Holdings”), incorporated in Canada, and Nova Park SAE (“Nova”), an Egyptian entity which owned the building in which the hotel * Fellow, St Catherine’s College and Professor of Law, University of Oxford. 1. Civil Procedure Rules 1998 (“CPR”), rr 6.36–6.37 and PD 6B (Service out of the jurisdiction). 2. [2017] UKSC 80; [2018] 1 WLR 192 (“ Brownlie ”), also noted A Briggs, post , 196. 3. The following summary of facts is taken from the judgment of Tugendhat J ( Brownlie v Four Seasons Holdings Inc [2014] EWHC 273 (QB)) and from the judgment of Lord Sumption in the Supreme Court ( Brownlie , [9–13]). 190